Soil Quality Investigation of an Abandoned Mine Area Using Geochemical and Geospatial Approach in Jantang Village - Nurul Aflah; Mulkal Mulkal; Muchlis Muchlis; Hendra Harisman; Alisastromijoyo Alisastromijoyo; Mirna Rahmah Lubis; Jessica Anggraini (Graduate Program of Syiah Kuala University, 2022)
The physical and chemical environmental impact in a mining area is inevitable, particularly for open pit mining areas. The impact could affect soil and water quality where mining activities, such as land clearing, blasting and hauling, occur. Thus, environmental monitoring in mining areas should be taken to measure the impact of mining activity for reclamation purposes. The objective of this research focuses on the measure of environmental impact on soil quality in terms of the nutrient content in an abandoned mine area at Jantang village, Lhoong, Aceh Besar. The research was conducted by collecting 15 soil samples, followed by laboratory analysis using atomic absorption spectrophotometry to investigate sampled 'soil's nutrients which are pH, Carbon (C-organic), Nitrogen (N-total), Phosphor (P-availability), and Ferro substance (Fe-concentration). In addition, to estimate the soil properties at locations outside the sampling area, a spatial interpolation method called inverse distance weight with an optimum power was used. The result shows that the soil is acidic, with low C-organic in the range of 0.02%–1.84%, N-total 0.02%–0.16%, and P-availability 0.55%–3.75%. In contrast, the Fe-concentration is very high, at 3000–3400 ppm.